A hot lunch for herbivores: physiological effects of elevated temperatures on mammalian feeding ecology. (7th September 2017) - Beale, Phillipa K.; Marsh, Karen J.; Foley, William J.; Moore, Ben D.
ABSTRACT: Mammals maintain specific body temperatures ( T b ) across a broad range of ambient temperatures. The energy required for thermoregulation ultimately comes from the diet, and so what animals eat is inextricably linked to thermoregulation. Endothermic herbivores must balance energy requirements and expenditure with complicated thermoregulatory challenges from changing thermal, nutritional and toxicological environments. In this review we provide evidence that plant‐based diets can influence thermoregulation beyond the control of herbivores, and that this can render them susceptible to heat stress. Notably, herbivorous diets often require specialised digestive systems, are imbalanced, and contain plant secondary metabolites (PSMs). PSMs in particular are able to interfere with the physiological processes responsible for thermoregulation, for example by uncoupling mitochondrial oxidative phosphorylation, binding to thermoreceptors, or because the pathways required to detoxify PSMs are thermogenic. It is likely, therefore, that increased ambient temperatures due to climate change may have greater and more‐specific impacts on herbivores than on other mammals, and that managing internal and external heat loads under these conditions could drive changes in feeding ecology.